Dynamical history of a binary cluster: Abell 3653 - Caglar, Turgay; Hudaverdi, Murat (OXFORD UNIV PRESS, 2017)
We study the dynamical structure of a bimodal galaxy cluster Abell 3653 at z = 0.1089 using optical and X-ray data. Observations include archival data from the Anglo-Australian Telescope, X-ray observatories XMM-Newton and Chandra. We draw a global picture for A3653 using galaxy density, X-ray luminosity and temperature maps. The galaxy distribution has a regular morphological shape at the 3 Mpc size. The galaxy density map shows an elongation in the east-west direction, which perfectly aligns with the extended diffuse X-ray emission. We detect two dominant groups around the two brightest cluster galaxies (BCGs). BCG1 (z = 0.1099) can be associated with the main cluster A3653E, and a foreground subcluster A3653W is concentrated at BCG2 (z = 0.1075). Both X-ray peaks are dislocated from the BCGs by similar to 35 kpc, which suggest an ongoing merger process. We measure the subcluster gas temperatures of 4.67 and 3.66 keV, respectively. Two-body dynamical analysis shows that A3653E and A3653W are very likely gravitationally bound (93.5 per cent probability). The highly favoured scenario suggests that the two subclusters have a mass ratio of 1.4 and are colliding close to the plane of sky (alpha = 17.61.) at 2400 km s(-1), and will undergo core passage in 380 Myr. The temperature map also significantly shows a shock-heated gas (6.16 keV) between the subclusters, which confirms the supersonic infalling scenario.
Keywords: galaxies: clusters: individual: Abell 3653; galaxies: clusters: intracluster medium; X-rays: galaxies: clusters; GALAXY CLUSTERS; VELOCITY DISPERSIONS; RICH CLUSTERS; XMM-NEWTON; NEARBY; MERGERS; MASS; Astronomy & Astrophysics